Wpływ diasporalnych grup nacisku politycznego na przebieg wyborów federalnych w Stanach Zjednoczonych na przykładzie „lobby pro-izraelskiego” - Karczewski, Maciej (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2015)
Celem artykułu jest określenie roli i znaczenia diasporalnych grup interesu w systemie politycznym Stanów Zjednoczonych oraz ocena ich realnego wpływu na przebieg wyborów federalnych w tym państwie. Przedmiotem analizy jest działalność żydowskich organizacji diasporalnych określanych potocznie mianem „lobby pro-izraelskiego”. W ramach postawionego problemu badawczego opisane zostały również narzędzia oraz mechanizmy wykorzystywane przez żydowskie grupy nacisku politycznego w zakresie wywierania wpływu na instytucje demokratyczne w USA.

Main purpose of this paper is to: 1) define the overall role of diaspora interest groups in American political system, and 2) assess their real impact on the course of the federal elections in the United States. The analysis has been narrowed to Jewish organizations commonly referred as „pro-Israel lobby” and their political activity. Author described main tools and mechanisms used by Jewish pressure groups to exert influence on democratic institutions in the US, in order to pursue their ethnic interests.
Diaspora interests groups and their impact on US federal elections. Case study: Israel lobby
Keywords: USA; diaspora; Izrael; lobby; USA; diaspora; Israel; lobby